The Effect of Job Seekers' Perception on Social Network Strategy in Nigeria - Anyim, Francis C.; Ngwama, Justice Chidi (NIU Journal of Humanities, 2022)
The job applicants' perception on the use of Social Network Strategy (SNS) for job search and other related activities has been tilted towards solving the problem of unemployment. The study examines the above subject with the objective of enhancing the use of SNS for job search in Nigeria. The study adopted a descriptive survey research design using questionnaire to elicit information from the respondents.  Purposive sampling technique was employed in selecting the organisations while the Systematic random sampling technique was used in selecting the respondents. A sample size of 188 was used from a population of 477 subjects and determined through Taro Yamane formula. The hypothesis was tested through the application of ANOVA statistics. The result shows that the mean differences between the different categories of social network users was significantly different along the level of usage (F3, 183 =21.153, p<0.05). The study indicated that the perception of job seekers has significant effect on the use of social network strategy. The study therefore, concluded that the perception of job seekers will significantly affect the use of social network strategy amongst other advantages or outcomes. The study therefore, recommended the creating of awareness on the usefulness of social network in job search in a bid to reduce the negative perception of the populace on its effectiveness as a viable option for job search in Nigeria. Keywords: Job Seekers, Perception, Social network, Job search, Applicants